Sistem Politik dan Pemerintahan Islam dalam Perspektif ‎Abu Al-A’la Al-Maududy - Idri Idri (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2008)
This article studies political and governmental concept in the perspective of Abu al-A’la al-Maududy, a Muslim intellectual from Pakistan. In the area of Islamic political thought, he has a distinct thought which he formulates in a theory he names teo-democracy. It is a synthesis of teocracy which sgnifies divine aspect and democrcy which denotes human affairs. Abu al-A’la al-Maududy along with Rashid Rida, is a thinker who desires a universal Islamic state , as it happened in the glorious past known by the name of khilafah (Islamic world state) and not nation state as it happens nowadays worldwide. I the application of trias politica, the nuance of teocracy is more dominant that democratic aspect. It is so because the bodies of legislative, executive as well as judicative should remain in the framework guidelined by God the Almihghty, the ultimate ruler.